Pengaruh Literasi Keuangan, Inklusi Keuangan, Financial Technology Terhadap Pengelolaan Keuangan UMKM Di Desa Talabiu Kecamatan Woha - Febriyanti Wildani; Armiani; Sofiati Wardah (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
This study aims to determine the influence of financial literacy, financial inclusion, and financial technology (fintech) on the financial management of Micro, Small, and Medium Enterprises (MSMEs) in Talabiu Village, Woha District. This research uses a quantitative approach with a saturated sampling technique, in which the entire population consisting of 95 MSME actors is used as the research sample. Data were collected using a questionnaire and analyzed using multiple linear regression with the assistance of SPSS version 25. The results indicate that partially, the three independent variables—financial literacy, financial inclusion, and fintech—have a significant effect on MSME financial management. Adequate financial literacy helps business owners plan and manage finances effectively and identify financial risks. Financial inclusion facilitates access to formal financial services such as business loans, savings, and working capital financing. The use of fintech enhances transaction efficiency, simplifies cash management, improves financial recording, and reduces administrative burdens. Simultaneously, the three variables contribute 58% to MSME financial management, while the remaining 42% is influenced by other factors not examined in this study, such as work productivity, entrepreneurial orientation, technology adoption, and product innovation.